Dietary and genetic influences on hemostasis in a Yup'ik Alaska Native population. - Nicholas T Au; Morayma Reyes; Bert B Boyer; Scarlett E Hopkins; Jynene Black; Diane O'Brien; Alison E Fohner; Joe Yracheta; Timothy Thornton; Melissa A Austin; Wylie Burke; Kenneth E Thummel; et al. (PLoS ONE)
Fish and marine animals are important components of the subsistence diet of Alaska Native people, resulting in a high ω3 PUFA intake. The historical record for circumpolar populations highlights a tendency for facile bleeding, possibly related to ω3 PUFA effects on platelet activation and/or vitamin K-dependent clotting factors. To evaluate these two scenarios in Yup'ik people of southwestern Alaska, we examined the association between dietary ω3 PUFA intake and activities of clotting factor II, V, fibrinogen, PT, INR, PTT, and sP-selectin in 733 study participants, using the nitrogen isotope ratio of red blood cells as a biomarker of ω3 PUFA consumption. sP-selectin alone correlated strongly and inversely with ω3 PUFA consumption. Approximately 36% of study participants exhibited PIVKA-II values above the threshold of 2 ng/ml, indicative of low vitamin K status. To assess genetic influences on vitamin K status, study participants were genotyped for common vitamin K cycle polymorphisms in VKORC1, GGCX and CYP4F2. Only CYP4F2*3 associated significantly with vitamin K status, for both acute (plasma vitamin K) and long-term (PIVKA-II) measures. These findings suggest: (i) a primary association of ω3 PUFAs on platelet activation, as opposed to vitamin K-dependent clotting factor activity, (ii) that reduced CYP4F2 enzyme activity associates with vitamin K status. We conclude that high ω3 PUFA intake promotes an anti-platelet effect and speculate that the high frequency of the CYP4F2*3 allele in Yup'ik people (~45%) evolved in response to a need to conserve body stores of vitamin K due to environmental limitations on its availability.